Electronic structure, magnetic ordering and X-ray magnetic circular dichroism in La₁₋xPrxCo₂P₂ phosphides - Bekenov, L.V.; Moklyak, S.V.; Antonov, V.N. (Condensed Matter Physics, 2015)
The electronic structure and magnetic ordering in La₁₋xPrxCo₂P₂ (x=0, 0.25, and 1) phosphides have been studied theoretically using the fully relativistic spin-polarized Dirac linear muffin-tin orbital (LMTO) band-structure method. The X-ray absorption and X-ray magnetic circular dichroism spectra at the Co L₂,₃ and Pr M₄,₅ edges have been investigated theoretically within the framework of the LSDA+U method. The core-hole effect in the final state as well as the effects of the electric quadrupole E₂ and magnetic dipole M₁ transitions have been investigated. Good agreement with experimental measurements has been found.